PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA, KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH DJP SUMATERA UTARA I - Nurdiana Tanjung (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The purpose of this study was to determine and analyze the effect of job satisfaction, work environment, leadership and work stress on employee performance in the North Sumatra DGT Regional Office I. The population in this study was 125 North Sumatra DGT Regional Office employees, with 125 sampling techniques using Slovin as many as 95 people. Based on the analysis results obtained value-t Job satisfaction = 2, 680, while t-table with dk 95 (attached) of 1.65, then t count t-table thus partially there is a significant influence between job satisfaction on performance, value t work environment = 2.992, while t-table with dk 95 (attached) is 1.65 then t count ˃t table thus partially there is a significant influence between the work environment on employee performance, t value of Leadership = 2,141 while t-table with dk 95 (attached) of 1.65 then t arithmetic t table thus partially there is a significant influence between Leadership on employee performance, t value of work stress = -1,812 while t-table with dk 95 (attached) of 1.65 then t count ˂ t table thus partially there is no negative effect between work stress on employee performance. F-count value of 14.765 while the value of F-table (attached) with the numerator dk 4 and the denominator dk 90 is equal to 2.48 where F-count F table (14.765 2.48), it can be stated that together (multiple) there is a positive and significant influence on job satisfaction, work environment, leadership, work stress on employee performance.